2005
DOI: 10.1038/nature04316
|View full text |Cite
|
Sign up to set email alerts
|

Structural mechanism of plant aquaporin gating

Abstract: Plants counteract fluctuations in water supply by regulating all aquaporins in the cell plasma membrane. Channel closure results either from the dephosphorylation of two conserved serine residues under conditions of drought stress, or from the protonation of a conserved histidine residue following a drop in cytoplasmic pH due to anoxia during flooding. Here we report the X-ray structure of the spinach plasma membrane aquaporin SoPIP2;1 in its closed conformation at 2.1 A resolution and in its open conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
878
2
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 776 publications
(922 citation statements)
references
References 46 publications
35
878
2
7
Order By: Relevance
“…Most residues that are in direct contact with the pores, especially those of the ar/R constriction region, are strongly conserved among PIP-type aquaporins, including the crystallized plasma membrane aquaporin SoPIP2;1 from spinach [13]. All 13 PIP1-and PIP2-type homologs from Arabidopsis contain an identical ar/R filter consisting of phenylalanine (Phe), histidine (His), threonine (Thr) and arginine (Arg).…”
Section: Simulation Of Small Solute Conduction In a Plant Aquaporinmentioning
confidence: 99%
“…Most residues that are in direct contact with the pores, especially those of the ar/R constriction region, are strongly conserved among PIP-type aquaporins, including the crystallized plasma membrane aquaporin SoPIP2;1 from spinach [13]. All 13 PIP1-and PIP2-type homologs from Arabidopsis contain an identical ar/R filter consisting of phenylalanine (Phe), histidine (His), threonine (Thr) and arginine (Arg).…”
Section: Simulation Of Small Solute Conduction In a Plant Aquaporinmentioning
confidence: 99%
“…A number of studies have also shown that AQPs play a role in various disorders from renal disease to cerebral oedema (Benarroch, 2007, Schrier andCadnapaphornchai, 2003) and even cancer (Yin et al, 2008, Chae et al, 2008. Consequently AQPs have been highlighted as key drug targets (Huber et al, 2012, Wang et al, 2006 although drugs that target AQPs for clinical use remain to be discovered. This diverse tissue distribution and involvement in many physiological and pathological processes, is summarised in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of certain serine residues activates some PIPs, and dephosphorylation rapidly closes them [26]. This aquaporin inactivation can prevent water loss from cells under drought or strong salt stress [16].…”
Section: Water Transport Of Barley Pipsmentioning
confidence: 99%